Valuation techniques : discounted cash flow, earnings quality, measures of value added, and real options - Larrabee, David T. (CFA Institute investment perspectives series., 2013)
Analysis and insights from top thought leaders on a pivotal topic in investing and asset management Valuation is the cornerstone for investment analysis, and a thorough understanding and correct application of valuation methodologies are critical for long-term investing success. Edited by two leading valuation experts from CFA Institute, this book brings together the insights and expertise of some of the most astute and successful investment minds of the past 50 years. From Benjamin Graham, the "father of value investing," to Aswath Damodaran, you'll learn what these investment luminaries have to say about investment valuation techniques, including earnings and cash flow analysis.-Features the best thinking on valuation from the industry's masters on the topic, supplemented with dozens of fascinating and instructive real-world examples -Comprehensively discusses special valuation situations, such as real options, employee stock options, highly leveraged firms, corporate takeovers, and more -Supplies you with the tools you need to successfully navigate and thrive in the ever-changing financial markets -Is being produced with the full support and input of CFA Institute, the world's leading association of investment professionals